Rare cause of pathological fracture in adults as hypophosphatemic rickets - J. M., Jeetendra Kumar; R., Mamatha T.; K. R., Divya Sharma; Gowda, Gowtham S. (International Journal of Advances in Medicine, 2019)
Hypophosphatemic rickets is a disorder of defective bone minerlization due to defect in renal phosphate handling process. It is characterised by increased phosphate excretion accompanied by increased phosphatonins like fibroblast growth factor 23. It can be hereditary form of X linked, autosomal dominant, autosomal recessive type of hypophosphatemic rickets. It is associated with low serum phosphorus, normal serum calcium, inappropriately low to normal vitamin D level. Correct identification of these disorders is important for determining therapy. Early diagnosis and management prevent subsequent complication of the disease.